STAGES OF IMPROVING THE POLICY OF SOCIAL PROTECTION OF THE POPULATION (Scientific Journal of Actuarial Finance and Accounting, 2024)
The article explores the concept of the socio-economic analysis of scientific sources carried out by scientists of four significant historical eras of the formulation and evolution of state social policy in the Western European countries, making the research problem pertinent. Scientific definitions of terms like "social sphere" and "social policy" by different writers and experts are provided in the scientific article. The paper also categorizes social protection programs, provides a thorough summary and analysis of the scientific and theoretical methods for enhancing their efficacy. After a thorough examination of the research materials, the author draws the conclusion that, in order to prevent a worsening of the economic downturn, it is urgent to improve population social protection measures.